The Narrative Structure of the Plot “Sleeping Beauty” in the French Folk Tale - Olga N. Patrakova (Studia Litterarum)
This article analyzes the structural and semantic features of the French folk tale “Sleeping Beauty,” which was recorded at the end of the 19th century by the folklorist L. Dardy in a remote corner of the Gascony. Due to the isolation of the region, this fairy tale not only contains elements of local culture but also maintains its archaic structure free from later literary influences. It allows us to identify the ancient core of the plot, which is associated with initiation rites and mythological ideas about circular time. In the structure of the fairy tale, there are 15 different functions. The narrative arrangement of these functions has several deviations from the traditional pattern and determines an important aspect of the plot that is relevant for its continuation in later literature and culture. One of these deviations is the doubling of function VIII, which involves villainy or lacking. This leads to a focus on two main characters, the victim and the seeker hero, and the simultaneous liquidation of villainy and lacking. Turning to the actions of the hero-seeker, the fairy tale “forgets” about the protagonist (Sleeping Beauty) for a while, who does not undergo traditional tests, does not engage in an open conflict with the antagonist, and does not win over the latter. Instead, she remains inactive for a significant part of the story, which creates a functional and semantic gap and contributes to the emergence of numerous later interpretations of the story filled with new motivations.